2016
DOI: 10.1177/0148607115627142
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Outcomes, and Management of Enteral Tube Feeding Intolerance: A Retrospective Cohort Study in a Tertiary Center

Abstract: ETFI is a frequent problem in adult hospitalized patients receiving ETF, and it is associated with poor clinical outcomes such as inadequate nutrition and complications of feeding. While the pathophysiology is poorly understood, there also appears to be no standard evidence-based treatment. Studies investigating the mechanisms and optimized management are therefore indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 27 publications
2
88
1
Order By: Relevance
“…Monitoring for EN intolerance often includes multiple parameters such as GRV and assessment of GI function 6 . In a recent observational study, Wang and colleagues 7 reported that 32% of patients receiving EN in a large tertiary hospital experienced enteral feeding intolerance. Of those patients, approximately two‐thirds demonstrated a single high GRV, whereas one‐third experienced a combination or 2 or more of the following symptoms: high GRV, nausea/vomiting, and abdominal distention.…”
Section: Section 10 Monitoring and Reassessmentmentioning
confidence: 99%
“…Monitoring for EN intolerance often includes multiple parameters such as GRV and assessment of GI function 6 . In a recent observational study, Wang and colleagues 7 reported that 32% of patients receiving EN in a large tertiary hospital experienced enteral feeding intolerance. Of those patients, approximately two‐thirds demonstrated a single high GRV, whereas one‐third experienced a combination or 2 or more of the following symptoms: high GRV, nausea/vomiting, and abdominal distention.…”
Section: Section 10 Monitoring and Reassessmentmentioning
confidence: 99%
“…Furthermore, Wang et al recently showed that delayed gastric emptying or gastroparesis, as measured by increased gastric residual volume, was the most frequently observed ETFI (63%) in hospitalized patients (n = 754), followed by nausea and vomiting (36%). Delayed food delivery to the small intestine has the potential to compromise the rate and magnitude of absorption in critically ill patients and, likely, all clinical populations.…”
Section: Methodsmentioning
confidence: 99%
“…However, ginger has most notably been studied for its ability to combat morning sickness, postoperative nausea and vomiting, and chemotherapy‐induced nausea and vomiting . A retrospective cohort study involving chart review of 754 hospitalized patients by Wang et al estimated that 36% of hospitalized patients receiving TFs experience nausea and vomiting. Similarly, a multicenter, prospective study of 298 hospitalized adults by Bloechl‐Daum and colleagues reported clinically relevant symptoms in up to 60% of patients undergoing chemotherapy, many of whom required TF support.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations